Dry Land Technology : factors and adoption /(Acc: 3410) - Singh, Raghunath, Dr. (Jodhpur : Agrobios (India), 2008)
Study confined to Jodhpur District, India.
Keywords: Arid regions agriculture; Dry farming; Agricultural innovations; Farmers